The irrationalities of rationality in police data processes - Huey, Laura (Policing and society, 2022)
This paper explores how police bureaucracies, in their pursuit of greater accountability and management efficiencies, create what are intended to be rational data collection and use processes. However, these processes often produce unintended consequences: namely, behaviours, practices, and policies that confound an organisation’s goals. Drawing on Ritzer’s McDonaldization thesis and qualitative data from two Canadian police organisations, we argue that although police bureaucracies focus on maintaining efficiency, calculability, predictability, and control when it comes to their data processes, not only do inaccuracies occur, but they happen because an over-emphasis on rational processes can produce forms of irrationality.